Cultivation of Spirulina platensis and Nannochloropsis oculata for nutrient removal from municipal wastewater - Sofiyah, Evi Siti; Suryawan, I Wayan Koko (Rekayasa, 2021)
Domestic wastewater contains a high average nutrient ammonia-N (NH3-N) and total phosphate (PO43--P). This nutrient content has the potential to cause eutropication in water bodies. To prevent this eutropication, it is necessary to treat domestic wastewater. Currently, processing technology is needed that is useful for improving the quality of processed wastewater and a small amount of byproduct. One of these technologies is processing with a microalgae system, where the algae can be used to become biodiesel. Two types of microalgae that have the potential to produce biodiesel are Spirulina platensis and Nannochloropsis oculate. The cultivation of the two types of microalgae was carried out in the domestic wastewater media of Jakarta City by providing 24-hour lighting with UV-A and UV-B. The specific growth rates of Spirulina platensis and Nannochloropsis oculate were not much different, namely 0.0279 h-1 and 0.0282 h-1. The microalgae Spirulina platensis and Nannochloropsis oculate respectively reduced NH3-N nutrients by 82% and 80%, while PO43-P was 65.2% and 63.7%. The pH value during processing shows in the normal pH range. Total dissolved solids (TDS) in the processing process also decreased in a span of 48 hours.